Initiation of the Development of a Bedside Handover Guideline in the Emergency Department of Hospital X - Hinoveva Natalia Joaquin; Hanny Handiyani; Andi Amalia Wilda; Harpendewisasmita Harpendewisasmita (Indonesian Journal of Global Health Research, 2025)
Emergency Department (ER) services are highly complex and carry significant risks to patient safety. Effective communication during the handover process is critical to improving patient safety and care quality. Bedside handover is a strategic form of communication between healthcare workers, ensuring that vital patient information—such as vital signs and urgent care needs—is conveyed accurately and directly, with involvement from both patients and families. The ISBAR communication tool provides a clear structure that helps reduce the risk of miscommunication. Objective to develop a guideline that serves as a consistent reference for nurses in performing bedside handover, fostering a culture of safety and high-quality care at Hospital X. Method: This study used a case report approach with both qualitative and quantitative methods to examine the nursing service system at Hospital X. Data were collected through interviews, document reviews, observations, and questionnaires, and analyzed using the nursing management function approach: planning, organizing, directing, and controlling. Questionnaires were distributed to unit leaders, unit coordinators, and all staff nurses working in Room X, with a total of 48 respondents with total sampling. In the Unfreezing Phase, many ER nurses resisted the bedside handover method, perceiving it as time-consuming and burdensome. Observations revealed continued reliance on traditional handover methods. In the Changing Phase, a Plan of Action (POA) was developed, including drafting supervision guidelines, conducting socialization, and evaluating bedside handover implementation. In the Refreezing Phase, bedside handover was expected to become standard practice, though implementation was limited by time constraints. The implementation of bedside handover in the ER, guided by Lewin’s Change Theory and structured through ISBAR, is a strategic step to ensure care continuity and improve patient safety.